Coping Strategies of Shadow Teachers Experiencing Burnout in an Inclusive Indonesian Elementary School: A Phenomenological Study - Hendra Budiono; Firman; Muhammad Sofwan; Marites Del Prado Antonio (Borneo Research and Education Center, 2026)
The crucial role of shadow teachers is often fraught with significant challenges. High workloads, constant demands to adapt to the diverse needs of children with special needs, lack of adequate training, and limited institutional support can trigger burnout. Therefore, concrete strategies are needed to address this issue. The aim of this study is to describe strategies for overcoming burnout in substitute teachers in inclusive elementary schools in Indonesia. Participants in this study were shadow teachers with a minimum of 3 years of work experience, considering that they would provide insight into dealing with children with special needs in inclusive classes during the daily teaching process. This study used a qualitative approach with a phenomenological research type. Broadly speaking, there are three main techniques in data collection: interviews, observation, and documentation. The results of the study show various strategies used by teachers in handling student tantrums, namely Seeking Social Support, Acceptance and Positive Values ​​(Emotionally Focused Coping), Managing Break Time and Self-Calming, Self-Development and Introspection, and Conducting Diversion Activities (Escape Avoidance). The findings suggest that mentor teachers do not rely on a single strategy but instead build a coping ecosystem that connects the professional realm (team discussions, self-evaluation) with the domestic/personal realm (family, diversional activities). The implications of this research suggest that inclusive teacher resilience is formed when the boundaries between work support and family support converge positively.